2010
DOI: 10.1186/1532-429x-12-34
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of global myocardial oxygenation in humans: initial experience

Abstract: PurposeTo assess the feasibility of our newly developed cardiovascular magnetic resonance (CMR) methods to quantify global and/or regional myocardial oxygen consumption rate (MVO2) at rest and during pharmacologically-induced vasodilation in normal volunteers.MethodsA breath-hold T2 quantification method is developed to calculate oxygen extraction fraction (OEF) and MVO2 rate at rest and/or during hyperemia, using a two-compartment model. A previously reported T2 quantification method using turbo-spin-echo seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Despite this early success for the quantification of myocardial OEF and MVO 2 during hyperemia, measuring OEF and MVO 2 by CMR at rest remains a challenge. Recently, McCommis et al [45] reported measurements of global OEF and MVO 2 in volunteers using a quantitative T 2 -preparation method and the results agreed favorably with other literature values. These techniques may allow comprehensive evaluation of alternations of myocardial oxygenation in the pathophysiology of subjects with myocardial ischemia [46].…”
Section: Methods For Quantitative Bold Imagingsupporting
confidence: 79%
“…Despite this early success for the quantification of myocardial OEF and MVO 2 during hyperemia, measuring OEF and MVO 2 by CMR at rest remains a challenge. Recently, McCommis et al [45] reported measurements of global OEF and MVO 2 in volunteers using a quantitative T 2 -preparation method and the results agreed favorably with other literature values. These techniques may allow comprehensive evaluation of alternations of myocardial oxygenation in the pathophysiology of subjects with myocardial ischemia [46].…”
Section: Methods For Quantitative Bold Imagingsupporting
confidence: 79%
“…The change of the myocardial consumption rate has been measured in volunteers using a single breath-hold T2 mapping technique [22]. …”
Section: Reviewmentioning
confidence: 99%
“…Surveillance of regional contractile and diastolic function, infarct size and fibrosis burden may be especially prudent as these parameters can uncover early or subtle benefits from therapy before there is global improvement in cardiac performance [140, 141]. Other measurable indices may also emerge as having important implications for cell engraftment, such as microvascular obstruction, myocardial blood flow, haemorrhage, oedema, area at risk and oxygenation [142, 143]. …”
Section: Integrated Imaging Of Cell Therapy In Clinical Studiesmentioning
confidence: 99%